Bladder Leiomyoma with Synchronous Solitary Fibrous Tumor of the Pleura - Charalampos Mavridis; George Georgiadis; Eleni D. Lagoudaki; Iordanis Skamagkas; Ioannis Heretis; Anastasios V. Koutsopoulos; Charalampos Mamoulakis (Case Reports in Urology)
Bladder leiomyomas (BLs) are extremely rare benign tumors of mesenchymal origin. The exact pathophysiological mechanisms that lead to their appearance remain unclear including hormonal disorders, chromosomal abnormalities, and fetal remnants in the bladder. They usually remain asymptomatic for a long period of time. Solitary fibrous tumors (SFTs) are also rare neoplasms of mesenchymal origin with malignant potential usually affecting the pleura. The pathogenesis of SFTs remains unclear. We report the case of a 28-year-old male presenting with SFT of the pleura and synchronous BL. The patient presented with persistent cough as a sole symptom. Computed tomography (CT) of the thorax revealed a pleural mass, which was surgically removed and proved to be a SFT. At an early follow-up, abdominal CT scan revealed a bladder wall mass that proved to be a BL. This is the first report of BL with synchronous SFT of the pleura. Synchronous BLs and SFTs may be incidental, but the coexistence of two mesenchymal tumors at different sites, in a young patient, may raise the suspicion of a new clinical syndrome that warrants further investigation.